Dataset on gene expression in the elderly after Mindfulness Awareness Practice or Health Education Program - Lim, H.; Saw, W.; Feng, L.; Lee, Y.; Mahendran, R.; Cheah, I.; Rawtaer, I.; Kumar, Alan Prem; Kua, E.; Mahendran, R.; Tan, E. (Elsevier Inc., 2018)
It has been reported that relaxation techniques can improve physical health and cognitive function. A number of studies involving different types of relaxation practices showed changes in expression of genes. We investigated the gene expression pattern of a cohort of elderly subjects of Asian descent after weekly (for the first three months) and monthly (for the subsequent six months) intervention. Sixty consenting elderly subjects (aged 60–90 years) with mild cognitive impairment were assigned to either the Mindfulness Awareness Practice (MAP) or Health Education Program (HEP) group in a randomized controlled trial to assess the effectiveness of the programs in preventing further cognitive decline and evaluate the influence on neurological, cellular and biochemical factors. Blood samples were collected before the start of intervention and after nine months for gene expression profiling using Affymetrix Human Genome U133 Plus 2.0 arrays. The dataset is publicly available for further analyses.